新加坡华语小剧场 ：以电力站（1990－2002年）为例 = Chinese language little theatre in Singapore : a case study of the Substation (1990-2002) - 张文豪 Teo, Eng Hao (2010)
“The Substation – A Home for the Arts” is Singapore first multi-disciplinary, multi-cultural arts centre. Founded by local theatre director, playwright Kuo Pao Kun in 1990, The Substation owned the first Black Box Theater in Singapore, and organised the “Raw Theatre season”, which propelled the growth of local Little Theatre (a mandarin term coined to describe small-scaled productions, usually with experimental or avant-garde nature), and even the whole development of local theatre. During the 90s, most Chinese Language Little Theatre were staged at The Substation, the rest was performed at non-theatrical space, for instance outdoors.